Reacquisition of New Meristematic Sites Determines the Development of a New Organ, the Cecidomyiidae Gall on Copaifera langsdorffii Desf. (Fabaceae) - Carneiro, Renê G. S.; Isaias, Rosy M. S.; Moreira, Ana S. F. P.; Oliveira, Denis C. (Frontiers in plant science, 2017)
The development of gall shapes has been attributed to the feeding behavior of the galling insects and how the host tissues react to galling stimuli, which ultimately culminate in a variable set of structural responses. A superhost of galling herbivores, , hosts a bizarre "horn-shaped" leaflet gall morphotype induced by an unidentified species of Diptera: Cecidomyiidae. By studying the development of this gall morphotype under the anatomical and physiological perspectives, we demonstrate the symptoms of the Cecidomyiidae manipulation over plant tissues, toward the cell redifferentiation and tissue neoformation. The most prominent feature of this gall is the shifting in shape from growth and development phase toward maturation, which imply in metabolites accumulation detected by histochemical tests in meristem-like group of cells within gall structure. We hypothesize that the development of complex galls, such as the horn-shaped demands the reacquisition of cell meristematic competence. Also, as mature galls are green, their photosynthetic activity should be sufficient for their oxygenation, thus compensating the low gas diffusion through the compacted gall parenchyma. We currently conclude that the galling Cecidomyiidae triggers the establishment of new sites of meristematic tissues, which are ultimately responsible for shifting from the young conical to the mature horn-shaped gall morphotype. Accordingly, the conservative photosynthesis activity in gall site maintains tissue homeostasis by avoiding hypoxia and hipercarbia in the highly compacted gall tissues.